2018
DOI: 10.2478/bjmg-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variability in two Macedonian families with Arterial tortuosity syndrome

Abstract: Arterial tortuosity syndrome (ATS) is a rare autosomal recessive disorder caused by mutations in the solute carrier family 2 member 10 (SLC2A10) gene encoding a glucose/ascorbic acid transporter. The clinical features of ATS are mild-to-severe tortuosity of the large and medium arteries throughout the body, accompanied by dysmorphisms and joint laxity. Vascular changes in different parts of the body lead to stenosis and/or aneurysms requiring difficult surgical procedures. Here we present two new patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A mortality rate of 40% was reported in patients under five years [ 9 ]. There is an increased risk for respiratory insufficiency, ventricular hypertrophy resulting in global heart failure, progressive myocardiopathy, aneurysm development, and dissection, which can involve the aortic root and potentially entire arterial tree [ 2 , 9 , 11 , 16 ]. Moreover, patients with ATS are susceptible to vascular ischemia involving cerebrovascular circulation, which may cause a non-hemorrhagic stroke and infarctions in the abdominal arteries at any age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mortality rate of 40% was reported in patients under five years [ 9 ]. There is an increased risk for respiratory insufficiency, ventricular hypertrophy resulting in global heart failure, progressive myocardiopathy, aneurysm development, and dissection, which can involve the aortic root and potentially entire arterial tree [ 2 , 9 , 11 , 16 ]. Moreover, patients with ATS are susceptible to vascular ischemia involving cerebrovascular circulation, which may cause a non-hemorrhagic stroke and infarctions in the abdominal arteries at any age.…”
Section: Discussionmentioning
confidence: 99%
“…A single case of ATS presenting with epilepsy was also reported, indicating that some patients presenting with epilepsy might need serious cerebral vascular evaluation [ 17 ]. A case with severe tortuosity of cerebral arteries causing migraine headaches has also been reported, suggesting that further attention is needed to investigate the intracranial blood flow changes in ATS cases [ 16 ]. In another rare case, Naunheim et al have observed persistent pulmonary hypertension and an association of venous tortuosity with ATS [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLUT10 is critical for cardiovascular development by facilitating both TGFβ signaling and mitochondrial respiration [24]. We found 24 patients affected by ATORS and with confirmed genetic diagnoses of SLC2A10 mutations [25][26][27][28][29]. ATORS is characterized by tortuosity of the aorta and middle-sized arteries, elongation, stenosis and aneurysm formation in major arteries, leading to disrupted elastic fibers in the medial layers of arterial walls [24,25].…”
Section: Glut10 Deficiencymentioning
confidence: 90%
“…ATS was initially described as a new type of EDS with tortuous systemic arteries 1 . Because of the discovery of causative mutations in SLC2A10 (GLUT10) in European and the Middle Eastern families, ATS was classified as a distinct syndrome 2‐9 . About 30 unique mutations have been identified in the SLC2A10 gene in ATS patients.…”
Section: Introductionmentioning
confidence: 99%
“…SLC2A10 (GLUT10) in European and the Middle Eastern families, ATS was classified as a distinct syndrome. [2][3][4][5][6][7][8][9] About 30 unique mutations have been identified in the SLC2A10 gene in ATS patients. We have previously described missense SLC2A10 mutations in 23 ATS patients belonging to the 13 consanguineous families from Qatar, Saudi Arabia, and Germany.…”
mentioning
confidence: 99%